An electronic referral system supporting integrated hospital discharge. Issue 2 (18th April 2017) - Wilberforce, Mark; Hughes, Jane; Clarkson, Paul; Whyte, David; Chester, Helen; Davies, Sue; Challis, David
Abstract : Purpose: The purpose of this paper is to evaluate the implementation and potential value of an electronic referral system to improve integrated discharge planning for hospitalised older adults with complex care needs. This new technology formed part of the "Common Assessment Framework for Adults" policy in England. Design/methodology/approach: Mixed methods were undertaken as part of a case study approach within an acute hospital in the North West of England. First, qualitative interviews were undertaken with practitioners to explore early experiences using the new technology. Second, routinely collected administrative data were analysed, comparing referrals made using the new technology and those made through the usual paper-based process. Findings: Qualitative interviews found that an electronic discharge system has, in principle, the potential to improve the efficiency and suitability of integrated care planning. However, the implementation proved fragile to decisions taken elsewhere in the local care system, meaning its scope was severely curtailed in practice. Several "socio-technical" issues were identified, including the loss of valuable face-to-face communication by replacing manual with electronic referrals. Research limitations/implications: The small number of patients referred during the implementation phase meant that patient outcomes could not be definitively judged. Research into the longer-term implications and value of electronic referral systems is needed. Originality/value: There is concern that attempts to integrate health and social care are stymied by incompatible systems for recording service user information. This research explores a novel attempt to share assessment information and improve support planning across health and social care boundaries.